问题 解答题
1
2
+
1
2
-
1
2
1
2
×
1
2
+
1
2
÷
1
2
1
2
-
1
2
)×88
13-48×(
1
2
+
1
2
1
2
÷3+
1
2
×
1
2
1
2
+
1
2
×
1
2
+
1
2
1
2
×
1
2
+
1
2
×
1
2
+
1
2
答案

(1)

1
2
+
1
2
-
1
2

=

1
2
+(
1
2
-
1
2

=

1
2
+0

=

1
2

(2)

1
2
×
1
2
+
1
2
÷
1
2

=

1
4
+1

=1

1
4

(3)(

1
2
-
1
2
)×88

=0×88

=0;

(4)13-48×(

1
2
+
1
2

=13-48×1

=13-48

=-35;

(5)

1
2
÷3+
1
2
×
1
2

=

1
6
+
1
4

=

5
12

(6)

1
2
+
1
2
×
1
2
+
1
2

=

1
2
+
1
4
+
1
2

=

1
2
+
1
2
+
1
4

=1+

1
4

=1

1
4

(7)

1
2
×
1
2
+
1
2
×
1
2
+
1
2

=

1
2
×(
1
2
+
1
2
+1)

=

1
2
×2

=1.

选择题
问答题 简答题